Ketergantungan Mahasiswa Dalam Penggunaan Instagram Guna Mencari Informasi - Roberto Maradutua; Tesalonika Manalu; Tiara Dharma (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
The widespread use of social media particularly Instagram among university students has significantly impacted various aspects of their lives. This study aims to analyze the patterns of Instagram usage as a source of information among students and its implications on digital dependency. The research methodology employed an online survey with participants from various students at the Indonesian Christian University. Data collection involved questionnaires assessing the frequency of Instagram usage for information-seeking purposes, the types of content sought, and the level of digital dependency. Descriptive and inferential statistical analyses were conducted to interpret the data. The primary findings indicate most students actively utilize Instagram as a source of information, particularly for non-academic content such as lifestyle and entertainment. Furthermore, a significant correlation was observed between Instagram usage patterns and students' levels of digital dependency. These findings underscore the importance of a deeper understanding of students' social media usage and the necessity of interventions to manage their digital dependencies effectively. The study contributes to the development of policies and intervention strategies aimed at addressing digital dependency issues among university students.